2001
DOI: 10.1104/pp.127.4.1854
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Phosphate Starvation-Induced Genes

Abstract: Phosphate (Pi) deficiency is a major nutritional problem faced by plants in many agro-ecosystems. This deficiency results in altered gene expression leading to physiological and morphological changes in plants. Altered gene expression is presumed to be due to interaction of regulatory sequences (cis-elements) present in the promoters with DNA binding factors (trans-factors). In this study, we analyzed the expression and DNA-protein interaction of promoter regions of Pi starvationinduced genes AtPT2 and TPSI1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
4
17
0
Order By: Relevance
“…In Arabidopsis thaliana nine highaffinity Pi transporter genes have been identified and characterized (Karthikeyan et al, 2002;Muchhal et al, 1996;Mudge et al, 2002;Okumura et al, 1998;Smith et al, 1997). There is growing evidence suggesting that plants in general have a small family of high-affinity Pi transporters (Muchhal et al, 1996;Mudge et al, 2002;Mukatira et al, 2001;Uta et al, 2002).…”
Section: Plant Phosphate Transportersmentioning
confidence: 94%
See 1 more Smart Citation
“…In Arabidopsis thaliana nine highaffinity Pi transporter genes have been identified and characterized (Karthikeyan et al, 2002;Muchhal et al, 1996;Mudge et al, 2002;Okumura et al, 1998;Smith et al, 1997). There is growing evidence suggesting that plants in general have a small family of high-affinity Pi transporters (Muchhal et al, 1996;Mudge et al, 2002;Mukatira et al, 2001;Uta et al, 2002).…”
Section: Plant Phosphate Transportersmentioning
confidence: 94%
“…Conserved MYB-factor-binding sequences have been identified in promoter regions of several P-starvation-inducible genes. In addition DNA-protein interaction studies revealed the existence of specific protein-binding domains (cis elements) in P-deficiency-induced genes including a Pi transporter (Mukatira et al, 2001). The DNA protein interaction was observed only under Pi sufficiency conditions, suggesting that some of the Pi-starvation-induced genes may be under negative regulation.…”
Section: Tissue-and Organ-specific Expression Of Pi Transportersmentioning
confidence: 97%
“…Unlike Pho4 in yeast (Kaffman and O'Shea 1999) and NUC-1 from N. crassa (Peleg et al 1996), the two putative transcriptional activators, Psr1 from Chlamydomonas and PHR1 from Arabidopsis, were shown to be permanently present in the nucleus (Wykoff et al 1999;Rubio et al 2001), thus suggesting a different type of Pi-starvation-dependent gene regulation than in yeast, maybe involving heterodimeric interactions between PHR1 and other MYB/CC proteins (Rubio et al 2001). Further evidence for a different type of regulation in plants was provided by Mukatira et al (2001). The authors could show by DNA mobility-shift assays that specific promoter sequences of two Pi-starvation-responsive genes interact with nuclear protein factors from Pi-sufficient plants, while the DNA binding activity disappeared during Pi starvation.…”
Section: Regulation Of Pi-transporter Gene Expressionmentioning
confidence: 95%
“…Specifi c interactions between the ARAthPht1;4 promoter and nuclear protein factors obtained from Pisuffi cient plants suggest that Pi -responsive genes are under a negative regulation (Mukatira et al, 2001 ). SPX domain (SYG1/Pho81/XPHR1) has been strongly related with signaling transduction pathway in Saccharomyces cerevisiae , Neurospora crassa , mouse, and human (Spain et al, 1995 ;Lenburg and O ' Shea, 1996 ;Peleg et al, 1996 ;Battini et al, 1999 ).…”
Section: Direct Phosphate Uptake Pathwaymentioning
confidence: 99%
“…It was proposed that AtSPX3 represses ARA;Pht1;4 and modulates Pi allocation, since spx3 plants show an enhanced expression of this transporter and higher Pi shoot concentrations (Duan et al, 2008 ). In rice, suppression of OsSPX1 resulted in the upregulation of OsPT2 and OsPT8 transporter genes under Pi -suffi cient conditions, leading to alter Pi uptake (Wang et al, 2009 ;Mukatira et al, 2001 ;Miura et al, 2005 ;Chen et al, 2008 ;Duan et al, 2008 ;Wang et al, 2009 ). The existence of negative mechanisms of regulation, however, does not preclude the action of a positive transcriptional control, but suggests a mechanism fi nely coordinated to maintain adequate cellular Pi levels, particularly when this nutrient is limited.…”
Section: Direct Phosphate Uptake Pathwaymentioning
confidence: 99%